Adaptation of training plans - Fister, I.; Fister Jr., I.; Fister, D. (Computational intelligence in sports, 2018)
In the last chapter, the automatic generation of sports training plans using CI algorithms was presented, where it was expected that the their realization would be proceeded smoothly. However, realization of the proposed training plan can be disrupted when an athlete in training process ill or is injured. These unpredictable events can interrupt the training process for a day or two, or even for several weeks. In this case, the training plan becomes unusable and must be adapted.